FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN USAHA TANI PADA TANAMAN UBI KAYU JENIS CASESA DIKANAGARIAN KAMANG DI KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Asriv, Desti - (Pendidikan Geografi, 2014)
This study aimed to obtain information, analyze and discuss data on the factors that affect thelevel of Revenue Farming In Cassava Plants type of Casesa in Kamang Village District of KamangBaru Sijunjung region seen from land, capital and labor skills.This type of research is descriptive correlational. The study population were all groups ofcassava farming in Kamang Village District of Kamang Baru Sijunjung region is divided into threeoblong farmer groups. The sample in this study were taken with a total sampling is by takingrespondents cassava farmers. The amount of the sample was 80 persons.The results showed: (1) there are significant land area to total revenue of cassava in KamangVillage District of Kamang Baru Sijunjung region because tcount> t table (6.818> 1.664), the effectof strong (r = 0.611) and a small contribution (37.3%) , (2) the influences of capital to operatingincome of cassava in Kamang Village District of Kamang Baru Sijunjung region because tcount> ttable (22.938> 2.00), the effect is very strong (r = 0.933) and the amount of the contribution is verylarge (87.1% ), (3) There is the influence of labor skills to operating income of cassava in KamangVillage District of Kamang Baru Sijunjung region because tcount> t table (1.748> 1.664), the effectis very low (r = 0.194) and a very small contribution (3.8% ) and (4) influences of land, capital andlabor skills together to operating income of cassava in Kamang Village District of Kamang BaruSijunjung region because of F> F table (207.134> 2.78). The magnitude of the effect of these threevariables to operating income of cassava in Kamang Village District of Kamang Baru Sijunjungregion categorized as very strong (r = 0.944), and included a very large contribution (89.1%)